0.25x-3=6x

Simple and best practice solution for 0.25x-3=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.25x-3=6x equation:



0.25x-3=6x
We move all terms to the left:
0.25x-3-(6x)=0
We add all the numbers together, and all the variables
-5.75x-3=0
We move all terms containing x to the left, all other terms to the right
-5.75x=3
x=3/-5.75
x=-3/5.75

See similar equations:

| 25*0.75*0.5=x | | 2x^2-3x-4=x+2 | | -9(b-5)=-11(b+4) | | x*0.75*0.5=9.44 | | -3 = f/25 | | x*0.75*0.5=9.4 | | x*0.75*0.5=94 | | 16j+15=-9+13j | | 21*0.75*0.6=x | | t/2+3=5 | | 7+4x5=x | | 16j+15=-9j+ | | x/8-1=-8 | | x*0.75*0.6=9,4 | | 9n=56+n | | x*0.75*0.5=9 | | 8/z+9=7 | | a-2=7-2a | | x+0.75*0.5=9 | | -16+2w=-2w | | 3x+17+0.5-5=180 | | 2n+9=6-3n | | X(1+7x)-6(-7-x)=36 | | 2x^2−3x−4=x+2 | | 2n+9-6=3n | | 2(9n-8)=-124 | | 3x+17+1/2x=180 | | 24-2x=-30 | | 2x2−3x−4=x+2 | | -4(6+n)-2=38 | | 4x+12+56=180 | | -25=5(n-4) |

Equations solver categories